DOP62 Immunogenicity to second anti-TNF therapy (IMSAT): Implications for sequencing of biologic therapy. (27th May 2021) - Chanchlani, N; Lin, S; Thomas, A; Hamilton, B; Nice, R; Chee, D; Kennedy, N; Goodhand, J; Ahmad, T
Abstract: Background: Anti-TNF (aTNF) treatment failure in patients with IBD is common. International guidelines recommend switching out of class when aTNF drug levels are therapeutic and within class with an immunomodulator when aTNF drug levels are suboptimal and associated with antibody development. We sought to define the: 1) risk of immunogenicity to a second aTNF stratified by immunogenicity to the first aTNF and 2) rates of drug persistence to a second aTNF in patients with pharmacodynamic or immunogenic failure of their first aTNF drug. Methods: We performed a retrospective cohort study across 32 UK hospitals. 870 patients (444 male, 630 (72%) Crohn's disease) who had both infliximab and adalimumab therapeutic drug monitoring performed by our service from May 2013 to November 2020 were identified. Drug and antibody levels were measured using the IDKmonitor® drug tolerant ELISA assays. Treatment failure included primary nonresponse, secondary loss of response, adverse drug reactions and IBD-related surgeries, and was identified by case note review. Immunogenic failure was defined as treatment failure with suboptimal drug levels (infliximab level <2 mg/L, adalimumab level <6 mg/L) with an antibody concentration ≥10 AU/ml. Pharmacodynamic failure was defined as treatment failure despite adequate drug levels. Results: Patients who developed immunogenicity to adalimumab (first) were more likely to develop immunogenicity to infliximab (second) (63% vs 40%, p = 0.004), and patients who developed immunogenicity to infliximab (first) were more likely to develop immunogenicity to adalimumab (second) (33% vs 19%, p = 0.002) (Fig 1). Patients who developed: antibodies and undetectable drug, low drug levels, or low drug levels with immunogenicity to infliximab (first), were more likely to develop these outcomes to adalimumab (second) (all p<0.001). There was no difference in drug persistence to second aTNF in patients with pharmacodynamic and immunogenic treatment failure (Fig 2). In patients with immunogenic (but not pharmacodynamic) failure, commencing an immunomodulator at the time of switching to second aTNF drug was associated with longer drug persistence than in patients treated with an immunomodulator throughout or not all (Fig 3). Conclusion: Immunogenicity to the first aTNF was associated with immunogenicity to the second aTNF, irrespective of drug sequence. Commencing an immunomodulator at the time of switching to second aTNF was associated with improved drug persistence in immunogenic, but not pharmacodynamic, failure. However, 50% of patients remained on second aTNF at 5 years in both groups, suggesting switching in-class may be appropriate irrespective of the cause of treatment failure to first aTNF.